A study of the information needs and uses of the students, faculty and research staff of the College of Forestry, University of the Philippines at Los Banos - Belen, Flor E. (1984)
This study is an attempt at identifying the information needs and uses of the students, faculty, and research staff of the College of Forestry, University of the Philippines at Los Banos, as well as assessing the use made of the College of Forestry Library Resources and Information Services.